Special Autonomy Fund and Privilege Fund Management in Indonesia: Literature Review Approach - Lak Lak Nazhat EL HASANAH; Dessy ISFIANADEWI; Unggul PRIYADI (Communications of International Proceedings, 2021)
This study aimed to determine the description and effectiveness of the Special Autonomy Fund and the Privileges Fund management. The Special Autonomy Fund and the Privileges Fund are part of the concept of asymmetric fiscal decentralization. This concept is applied to develop the region's economy with management following the proposal and agreed upon by the central government. Differences in the control of each area will have different impacts. Asymmetric fiscal decentralization was given to the regions of Aceh, Papua, and Yogyakarta. The method used in describing the management and effectiveness of the Special Autonomy and Special Autonomy funds in this study was carried out with a Literature Review approach. The management of the Special Autonomy Fund and the privileged fund has a different legal basis and purpose. It is hoped that through the proper allocation and management of the Special Autonomy Fund and the Privileges Fund, there will be changes in the welfare of the people in the region. However, in general, it can be described that the management of these funds in Aceh, Papua, and Yogyakarta is still not optimal. There has not been a significant reduction in poverty and economic disparities between regions.
Keywords: Special Autonomy Fund; Privileges Fund; Management; Effectiveness